2014
DOI: 10.1371/journal.pone.0111779
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic and Genome-Wide Deep-Sequencing Analyses of Canine Parvovirus Reveal Co-Infection with Field Variants and Emergence of a Recent Recombinant Strain

Abstract: Canine parvovirus (CPV), a fast-evolving single-stranded DNA virus, comprises three antigenic variants (2a, 2b, and 2c) with different frequencies and genetic variability among countries. The contribution of co-infection and recombination to the genetic variability of CPV is far from being fully elucidated. Here we took advantage of a natural CPV population, recently formed by the convergence of divergent CPV-2c and CPV-2a strains, to study co-infection and recombination. Complete sequences of the viral coding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
77
3
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(87 citation statements)
references
References 46 publications
6
77
3
1
Order By: Relevance
“…In addition to high rates and positive selection of mutations in the viral capsid gene, previous studies have reported that genetic recombination has an important factor in the generation of viral diversity and the emergence of new genotypes (Wang et al, 2012;Pérez et al, 2014). However, we not observed evidence about recombination events in strains from Belém reported in this study.…”
Section: Discussioncontrasting
confidence: 86%
“…In addition to high rates and positive selection of mutations in the viral capsid gene, previous studies have reported that genetic recombination has an important factor in the generation of viral diversity and the emergence of new genotypes (Wang et al, 2012;Pérez et al, 2014). However, we not observed evidence about recombination events in strains from Belém reported in this study.…”
Section: Discussioncontrasting
confidence: 86%
“…Comparison with VP2 sequences available in the GenBank database shows that this change occurred into CPV‐2a/CPV‐2b sequences from Asia (Chinchkar et al., ; Wu et al., ), Brazil (Pereira, Leal, & Durigon, ) and Europe (Cságola et al., ), including Italy (isolate CPV‐2a/151/212—accession n. ). The same mutation was also found in CPV‐2c strains collected in 2011‐2012 in Uruguay (Pérez et al., ) and Ecuador (Aldaz et al., ).…”
Section: Resultssupporting
confidence: 61%
“…Sequencing of the complete genome, encompassing both NS and VP genes, was carried out using primers pairs NS‐Fext (5′‐GACCGTTACTGACATTCGCTTC‐3′)/NS‐Rext (5′‐GAAGGGTTAGTTGGTTCTCC‐3′) and 2161F (5′‐TTGGCGTTACTCACAAAGACGTGC‐3′)/4835R (5′‐ACCAACCACCCACACCATAACAAC‐3′) (Pérez et al., ), using two separate reactions and the same reaction mix and thermal conditions described above. Amplicons were purified with Illustra™ GFX™ PCR DNA and Gel Band Purification Kit (GE Healthcare Life Sciences, Amersham, Buckinghamshire, UK) and submitted to BMR Genomics srl (Padova, Italy) for direct Sanger sequencing with additional internal primers: NS‐Fint (5′‐GTTGAAACCACAGTGACGACAG‐3′) for the PCR product amplified with primers pair NS‐Fext/NS‐Rext, R2 (5′‐TTTTGAATCCAATCTCCTTCTGGAT‐3′) and 3475R (5′‐GTTGGTGTGCCACTAGTTCCAGTA‐3′) for the product amplified with primers pair 2161F/4853R.…”
Section: Methodsmentioning
confidence: 99%
“…Limited studies are available on the CPV non‐structural genes (Hoelzer et al, ; Pérez et al, ), and, only recently, the analysis of the NS1 gene sequence was included in the CPV phylogenies from several countries (Canuti, Rodrigues, Whitney, & Lang, ; Grecco et al, ; Mira, Canuti, et al, ; Mira, Purpari, et al, ; Zhuang et al, ). In this study, sequence analysis revealed aa changes previously described mainly in NS1/NS2 gene sequences of CPV‐2a/2c strains of Asian origin.…”
Section: Discussionmentioning
confidence: 99%
“…By excluding the VP2 gene sequences with complete nt identities, 8 CPV DNAs from different cities of collection were further selected for a further sequence analysis by amplifying a long genome sequence encompassing both major ORFs, without the 5′ and 3′ flanking sequences (Table ). Sequence analyses were carried out using primer pairs described by Pérez et al (), using the commercial kit GoTaq ® G2 DNA Polymerase (Promega Italia s.r.l. ), as previously described (Mira, Dowgier, et al, ) with minor modifications (Mira, Canuti, et al, ).…”
Section: Methodsmentioning
confidence: 99%